The Reconfiguration of Network at 20 kV Distribution System Nagan Raya Substation with the Addition of the Krueng Isep Hydroelectric Power Plant - Ediwan, Ediwan; Muliadi, Muliadi; Mahalla, Mahalla; Nazaruddin, Nazaruddin; Mulkan, Andi (Jurusan Teknik Elektro Universitas Andalas, 2021)
Switching substations are usually supplied from one express feeder which can cause a low level of reliability due to disruption or outage on the express feeder. Also, the lack of power supply at the ends of the network causes voltage drops. One way to solve this problem is to reconfigure the network. In this study, testing was carried out on a distribution system in the Nagan Raya Regency, namely the distribution system of PT. PLN (Persero) ULP Jeuram originally had a radial system. Furthermore, the distribution system was reconfigured with the Krueng Isep hydroelectric power plant which was included in the PLN ULP Jeuram grid so that the system that was originally radial became a loop configuration. The method used in analyzing the network reconfiguration process is to use the ETAP 12.6 application. As a result, after reconfiguring the network the voltage increased from 19.2 kV to 20.7 kV, the highest increase was at the Beutong Substation which reached 1.5 kV and decreased power losses in the network with a total of 188.2 kW and 263.1 kVAR. Furthermore, before the network reconfiguration, ULP Jeuram SAIFI value was 22.25 times/customers and SAIDI values 1337.74 minutes/ customers. However, after reconfiguring the network, ULP Jeuram SAIFI value fell to 15.39 times/customers and SAIDI to 945.6 minutes/customers, resulting in an increase in system reliability by 70.69%.Keyword:Â Reconfiguration of network, distribution system, hydroelectric power plant, SAIDI, SAIFIÂ